HUBUNGAN ANTARA KUALITAS TIDUR DENGAN DAYA INGAT JANGKA PENDEK PADA MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN DAN PROFESI DOKTER ANGKATAN TAHUN 2019, FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Cindranela, Ervina (E-Jurnal Medika Udayana, 2022)
Quality sleep is beneficial for the body's regulatory processes and cognitive functions such as memory. Memory is the process of changing and responding to information to adapt to the external environment. Changes in environmental patterns and behavior have an impact on sleep quality and memory. The population at risk for this impact is students. This study was conducted to determine the correlation between sleep quality and short-term memory with a cross sectional study. This research was conducted to 45 Udayana Medical students. The measuring instruments used were the Pittsburgh Sleep Quality Index (PSQI) and the Short-Term Memory Digit Span Test. Of 45 respondents, it was found that the distribution of sleep quality was 22.2% of respondents with good sleep quality, 13.3% of respondents with adequate sleep quality and 64.4% of respondents with poor sleep quality. The average short-term memory of respondents was 19.20. The results of the Spearman's Rank correlation test obtained a significance value of 0.426 (p> 0.05). There was no significant correlation between sleep quality and short-term memory. Keywords: sleep quality, short-term memory, PSQI, Short-Term Memory Digit Span Test